2012
DOI: 10.1159/000338273
|View full text |Cite
|
Sign up to set email alerts
|

Weeklynab-Paclitaxel in Metastatic Breast Cancer – Summary and Results of an Expert Panel Discussion

Abstract: Taxanes are regarded as the most effective single agents in the treatment of metastatic breast cancer (MBC). For conventional taxanes, crucial toxicities and impairments in clinical efficacy are related to solvents necessary because of the agents’ hydrophobicity. The mandatory premedication with corticosteroids causes additional side effects. Nab-paclitaxel is a solvent-free colloidal suspension of paclitaxel and human serum albumin that exploits the physiological transport properties of albumin. It is registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…Although the interpretation of the results of cross-study comparison needs to be made with caution, the ORR for oral DHP107 in this study compares favorably with that reported by studies of first-line IV paclitaxel 18 and IV nab-paclitaxel 20,21 monotherapy in the treatment of metastatic breast cancer. In a review of studies conducted in the 1990s, Vogel and Nabholtz 18 reported ORRs of 15–62% with IV paclitaxel.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although the interpretation of the results of cross-study comparison needs to be made with caution, the ORR for oral DHP107 in this study compares favorably with that reported by studies of first-line IV paclitaxel 18 and IV nab-paclitaxel 20,21 monotherapy in the treatment of metastatic breast cancer. In a review of studies conducted in the 1990s, Vogel and Nabholtz 18 reported ORRs of 15–62% with IV paclitaxel.…”
Section: Discussionsupporting
confidence: 75%
“…In a review of studies conducted in the 1990s, Vogel and Nabholtz 18 reported ORRs of 15–62% with IV paclitaxel. Jackisch et al 21 reported ORRs of 38–49% for studies of weekly IV nab-paclitaxel. A study of IV nab-paclitaxel in routine clinical practice reported an ORR of 9% (one of 11 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, nab-paclitaxel is accepted in both weekly or 3-weekly regimens [23]. In the present study, patients treated with a weekly regimen showed longer PFS and higher ORR compared to those treated with a 3-weekly regimen.…”
Section: Discussionmentioning
confidence: 49%
“…However, 40.2% of patients in this cohort received nab-paclitaxel as first-line therapy, and only 15.4% received nab-paclitaxel as 4th or later lines of treatment [ 22 ]. Currently, nab-paclitaxel is accepted in both weekly or 3-weekly regimens [ 23 ]. In the present study, patients treated with a weekly regimen showed longer PFS and higher ORR compared to those treated with a 3-weekly regimen.…”
Section: Discussionmentioning
confidence: 99%
“…[62]. Beim Mammakarzinom wird es in der Praxis inzwischen neben der 3-wöchentlichen Gabe in der Dosierung von 260 mg/m 2 bevorzugt in einer Dosierung von wöchentlich 125 mg/m 2 über 3 Wochen mit einer Woche Therapiepause (qw3/4) eingesetzt [63]. Im Hinblick auf den Einsatz und die zu wählende Dosierung von nab-Paclitaxel in der metastasierten Situation bei Frauen mit HER2-negativem und endokrin nicht empfindlichem Mammakarzinom schließen wir uns einer bereits im Jahr 2012 von einem Expertenpanel formulierten Empfehlungen an [63] und verweisen auf die im März 2019 publizierten Leitlinien der AGO, Kommission Mamma.…”
Section: Taxan Der Zweiten Generation: Nab-paclitaxelunclassified